2020
DOI: 10.1080/23802359.2020.1840933
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of the millipede Epanerchodus koreanus Verhoeff, 1937 collected in limestone cave of Korea (Polydesmidae: Polydesmida)

Abstract: We have determined the second mitochondrial genome of Epanerchodus koreanus Verhoeff, 1937 collected in limestone cave of Korea. The circular mitochondrial genome of E. koreanus is 15,581 bp long. It includes 13 protein-coding genes, two ribosomal RNA genes, and 22 transfer RNA genes. Its gene order was different from the rest three Polydesmida mitochondrial genomes, resulted from relocation of tRNAs, rRNAs, and ND1. The base composition was AT-biased (75.1%). Phylogenetic trees displayed phylogenetic relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…The base compositions of the two genomes were almost the same. Base composition analysis showed that the whole mitogenomes of Polydesmida species were biased towards A and T ( Table 3 ), from 64.04% for Appalachioria falcifera to 75.11% for Epanerchodus koreanus , which was the same as in previous studies [ 33 ]. Additionally, the A + T% of PCGs, rRNAs, and tRNAs in Polydesmida species were also higher than the G + C%.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The base compositions of the two genomes were almost the same. Base composition analysis showed that the whole mitogenomes of Polydesmida species were biased towards A and T ( Table 3 ), from 64.04% for Appalachioria falcifera to 75.11% for Epanerchodus koreanus , which was the same as in previous studies [ 33 ]. Additionally, the A + T% of PCGs, rRNAs, and tRNAs in Polydesmida species were also higher than the G + C%.…”
Section: Resultssupporting
confidence: 81%
“…These lengths were well within the range found in other species of Polydesmida. Each mitogenome contained 13 PCGs, 19 tRNAs, 2 rRNAs, and one CR, which was different from typical sets of genes found in invertebrate mitogenomes in terms of the lack of trnI , trnL2 , and trnV [ 33 ]. The genes of both mitogenomes were all situated on the minor strand (N-stand), a characteristic shared with other species of Polydesmida [ 20 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with individual genes, the mitogenome remains a promising tool for inferring phylogenetic relationships due to its high information content. Recently, some mitogenomes in Diplopoda were published and applied to explore phylogenetic relationships [ 13 , 14 , 15 , 16 ]. However, only a few mitogenomes have been published for Spirobolida [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“… 2009 ; Li 2013 ) available in the Genome Information System ( http://geis.infoboss.co.kr/ ) utilized in the previous organelle genomic studies (Joo et al. 2020 ; Lee et al. 2020 ; Park, Xi, Oh, 2020 ; Jung et al.…”
mentioning
confidence: 99%